Implementasi Nilai Filsafat Pendidikan Islam dalam Proses Pembelajaran di Institut K.H Ahmad Sanusi - Dadang Sahroni; Diya Atul Millah; Septy Premitha; Sinta Puspita; Nessya Aenur Zammil (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2026)
Islamic Educational Philosophy holds a pivotal role in directing the learning process to remain consistent with Islamic principles. This article seeks to explore how the values of Islamic Educational Philosophy are implemented in the learning activities at the Institute of KH Ahmad Sanusi, with a focus on fourth-semester students. The study adopts a qualitative approach using a descriptive-analytical design based on library research and the examination of instructional practices. The results reveal that Islamic Educational Philosophy serves as a conceptual framework for determining and applying learning strategies, including discussion and inquiry-based learning, which foster active participation, critical thinking, and the internalization of Islamic values. Learning assessment is carried out in a comprehensive manner by addressing cognitive, affective, and psychomotor domains through individual assignments, collaborative tasks, formal examinations, and academic writing activities. Moreover, the emphasis on self-reflection (muhasabah) enhances students’ awareness of their moral and spiritual responsibilities in the process of seeking knowledge. The application of Islamic Educational Philosophy is therefore expected to support the development of students who are intellectually competent, morally grounded, and reflectively aware as future educators and Muslim intellectuals.